2013
DOI: 10.1097/ta.0b013e318270d967
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life one year after a road accident

Abstract: Prognostic study, level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 18 publications
3
18
1
Order By: Relevance
“…We also examined whether the identification of subclinical PTSD could identify participants at risk of future psychological disorders. Although our sample size was small (n = 13), we found that early subclinical PTSD was similar to clinical PTSD in terms of its relationship to having any Research has reported that premorbid psychiatric problems is associated with poor post-injury outcomes [38][39][40]. In the current study, 25% of respondents reported a history of psychological diagnosis, which is similar to the 12-month prevalence of psychological disorders in the Australian general population [41].…”
Section: Influence Of Early Psychological Diagnosis On Later Psycholosupporting
confidence: 67%
“…We also examined whether the identification of subclinical PTSD could identify participants at risk of future psychological disorders. Although our sample size was small (n = 13), we found that early subclinical PTSD was similar to clinical PTSD in terms of its relationship to having any Research has reported that premorbid psychiatric problems is associated with poor post-injury outcomes [38][39][40]. In the current study, 25% of respondents reported a history of psychological diagnosis, which is similar to the 12-month prevalence of psychological disorders in the Australian general population [41].…”
Section: Influence Of Early Psychological Diagnosis On Later Psycholosupporting
confidence: 67%
“…The SF-36 Summary Scores increased over time and can show the health development of injured patients toward an improvement of physical and mental status. Outcomes research on injured patients has shown that health-related quality of life increases in the long run 1,2,5,6,8,18,5255. Compared to the healthy population, the level of our study patients’ health-related quality of life 12 months after discharge from the hospital was still low, which is characteristic of accident victims at this date 1,6,8,56.…”
Section: Discussionmentioning
confidence: 62%
“…Poor physical well-being can additionally impact economic well-being, given the high cost of health care in the United States. Serious-injury vehicle accidents are especially financially damaging for victims due to the burden of medical costs and potential lost income from the interruption of work (Khati et al, 2013). …”
Section: A Framework For Transportation-related Quality Of Lifementioning
confidence: 99%